Experimental Study of an Evaporative Cooling System in a Rotating Vertical Channel with a Circular Cross-Section for Large Hydro-Generators - Ruiwei Li; Lin Ruan (Energies)
With the evolution of hydroelectric generators toward larger capacity and higher rotational speeds, the significa++nt increase in power density has rendered rotor cooling technology a critical bottleneck restricting performance enhancement. Addressing the need for feasibility verification and thermodynamic characteristic analysis of evaporative cooling applied to rotors, this study innovatively proposes an internal-cooling-based evaporative cooling architecture for rotor windings. By establishing a single-channel experimental platform for a rotor evaporative cooling system, the key parameters of the system circulation flow under varying centrifugal accelerations and thermal loads are obtained, revealing the flow mechanism of the cooling system. The experimental results demonstrate that the novel architecture has outstanding heat dissipation performance. Furthermore, the experimental findings reveal that the flow characteristics of the medium are governed by the coupled effect of centrifugal acceleration and thermal load; the flow rate decreases with increasing centrifugal acceleration and increases with rising thermal load. Centrifugal acceleration reduces frictional losses in the heating pipe, leading to a decrease in the inlet–outlet pressure difference. Through the integration of experimental data with classic formulas, this study refines the friction factor model, with the modified formula showing a discrepancy of −10% to +5% compared with the experimental results. Finally, the experiment was rerun to verify the universality of the modified friction factor.